2023
DOI: 10.1097/nnr.0000000000000700
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Race, Ethnicity, and Maternal Education on Infant Mortality

Rahshida Atkins,
Nancy M. H. Pontes,
Natasha A. Patterson
et al.

Abstract: Background The state of New Jersey has a large Black/African American (AA) versus White racial disparity in infant mortality and educational level at childbirth. This disparity, measured by rate ratio, increases with greater maternal education among varied racial–ethnic groups. The nature of this disparity measured by rate differences has not been explored. Objectives Infant birth and mortality data were used to examine whether racial or ethnic disparit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(74 reference statements)
1
0
0
Order By: Relevance
“…The risk of infant mortality, PTD and SGA significantly differs by race/ethnicity; after adjustment for HDP and other demographic and clinical characteristics, we found that infant mortality rates continue to be higher among NHB mothers (RR = 1.43; 95% CI: 1.30–1.57) in comparison to NHW mothers as seen in other studies [ 17 , 29 , 30 ]. In 2020, infant mortality rates in both the U.S. and SC were 6.5 infant deaths per 1000 live births; however, infant mortality rates differed greatly in SC for women of White and Black/Other races with 4.5 and 10.8 infant deaths per 1000 live births, respectively [ 31 ].…”
Section: Discussionsupporting
confidence: 76%
“…The risk of infant mortality, PTD and SGA significantly differs by race/ethnicity; after adjustment for HDP and other demographic and clinical characteristics, we found that infant mortality rates continue to be higher among NHB mothers (RR = 1.43; 95% CI: 1.30–1.57) in comparison to NHW mothers as seen in other studies [ 17 , 29 , 30 ]. In 2020, infant mortality rates in both the U.S. and SC were 6.5 infant deaths per 1000 live births; however, infant mortality rates differed greatly in SC for women of White and Black/Other races with 4.5 and 10.8 infant deaths per 1000 live births, respectively [ 31 ].…”
Section: Discussionsupporting
confidence: 76%